Financial Managers as Policy Makers and Company Relations with Financial Markets - Hermawan, Eric (Journal of Law, Politic and Humanities, 2021)
Financial Management means planning, organizing, directing, and controlling economic activities such as procurement and utilization of company funds. Financial Management itself has several principles that must be considered to be used by financial managers to minimize company costs while maximizing company profits. These principles are divided into 4 points: Accountability, Consistent, Transparent, and Integrity. The financial manager is no less critical and can be considered the spearhead of a company. Financial managers have various roles that depend on the company's situation and complexity. This study indicates that financial managers have a role and function as a liaison between companies and productive financial markets. The method used in this research is the descriptive qualitative method and library research, where the data collection is taken from various sources that exist and can be accounted for.